Characterization of the complete mitochondrial genome of the red crayfish, Procambarus clarkii (Decapoda: Cambaridae). (2nd September 2016) - Liu, Qiu-Ning; Chai, Xin-Yue; Jiang, Sen-Hao; Zhou, Chun-Lin; Xuan, Fu-Jun; Tang, Bo-Ping
Abstract: Here we present the complete mitochondrial (mt) genome of Procambarus clarkii (Decapoda: Cambaridae) and provide its annotation. The complete mt genome was determined to be 15 929 bp and contains 22 tRNA genes, 13 protein-coding genes (PCGs), two rRNA genes, and a D-loop region. The nucleotide composition was biased toward A + T nucleotides (72.91%) and the AT skew of this mt genome was slightly negative. All the 22 tRNA genes displayed a typical clover-leaf structure, with the exception of trnS1 (AGN). About 13 PCGs were initiated by ATN codons, except for cox1 and nad2 genes which were initiated by ACG and GTG, respectively. Six of the 13 PCGs harbor the incomplete termination codon by T or TA. The D-loop region of the mt genome was 1188 bp in length and the A + T content was 81.08%. Phylogenetic analysis showed that the placement of P. clarkii was within the Cambaridae. This mt genome sequence will provide a better understanding for crayfish evolution in the future.